Establishing norms for the sixteen personality factor test (16 PFQ) a preliminary study - Jose, Marietta (Alday) 1933-
Having known the advantage of using relevant norms for a more meaningful interpretation of test scores, the researcher made preliminary attempts to investigate the 16 PF with the end in view of developing norms which may serve as more accurate bases for Filipino Ss.